Rancangan Konten Desa Wisata Kampoeng Dolanan Eyang R. Tjokrowihardjo pada Media Google Sites untuk Walitelon Utara Temanggung - CINDY CITYA DIMA (Media Wisata, 2022)
Design of tourism village content of Kampoeng Dolanan Eyang R. Tjokrowihardjo on google sites media for the north walitelon of Temanggung. The use of Google Sites can increase Pokdarwis competence and general public visits as digital literacy readers. Specific targets to be achieved are orderly administration for Pokdarwis workshops and at the same time as promotional media with google sites for the general public. The method used is a qualitative descriptive (phenomenon) because the Covid 19 pandemic phenomenon is still a scourge for tourism, especially tourist villages. This study uses data triangulation for data collection from the master trainer from the Ministry of Tourism and Creative Economy of the Republic of Indonesia during a visitation assessment of assistants from universities in the tourist village of Walitelon Utara, Temanggung in November 2020, observation of tourism village content on google sites, as well as surveys of potential users. This page and with data analysis techniques, namely editing in addition to the media, the content is also in line with the assistance of the Higher Education. The author gives the name "Desa Wisata Walitelon Utara" sites.google.com